Status of learner autonomy in English language learning among EFL learners in Chinese vocational and technological colleges - Li, Yitan; Ismail, Lilliati; Mohamed Razali, Abu Bakar (Human Resources Management Academic Research Society (HRMARS), 2024)
This study explored the status of learner autonomy in English language learning among English as a Foreign Language (EFL) learners attending Chinese vocational and technological colleges. In Chinese research on the autonomous learning of EFL learners, there has been little focus on the EFL learners in Chinese vocational and technological colleges. Due to factors such as language foundation and learning environment, studies primarily focusing on undergraduates cannot fully apply to EFL learners in vocational and technological colleges. Therefore, this study targets 10 EFL learners randomly chosen in a vocational and technological college, using semi-structured interviews to explore the current state of their autonomous learning. The investigation’s results reveal that influenced by the examination-oriented education system, Chinese EFL learners in vocational and technological colleges have a relatively limited understanding of autonomous learning, demonstrate an excessive reliance on their instructors, engage in a limited range of autonomous learning activities, and lack a deficiency in fundamental proficiency on learning strategies. The results of this study will assist EFL teachers in vocational and technological colleges in gaining better insights into their students, allowing them to choose more effective teaching methods.